2007
DOI: 10.1681/asn.2006121304
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Vascular Rarefaction and Reduced VEGF-A Expression in Human Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is a frequent complication in patients with diabetes. Although the majority of DN models and human studies have focused on glomeruli, tubulointerstitial damage is a major feature of DN and an important predictor of renal dysfunction. This study sought to investigate molecular markers of pathogenic pathways in the renal interstitium of patients with DN. Microdissected tubulointerstitial compartments from biopsies with established DN and control kidneys were subjected to expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
181
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(203 citation statements)
references
References 52 publications
15
181
3
4
Order By: Relevance
“…The finding of glomerular VEGFA and FLT1 induction in NSC biopsy specimens is in contrast to the reduced expression of VEGFA recently reported in human diabetic nephropathy both in glomeruli and in the tubulointerstitial compartment, indicating a different pathophysiological mechanism for glomerulosclerosis in NSC and diabetic nephropathy. 33,45 HIF target genes involved in the accumulation of extracellular matrix and fibrosis were also found to be induced in glomeruli with NSC. This finding was confirmed by RT-PCR for FN1, for which HIF-independent regulatory mechanisms are also described, 46 and for LOXL2.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The finding of glomerular VEGFA and FLT1 induction in NSC biopsy specimens is in contrast to the reduced expression of VEGFA recently reported in human diabetic nephropathy both in glomeruli and in the tubulointerstitial compartment, indicating a different pathophysiological mechanism for glomerulosclerosis in NSC and diabetic nephropathy. 33,45 HIF target genes involved in the accumulation of extracellular matrix and fibrosis were also found to be induced in glomeruli with NSC. This finding was confirmed by RT-PCR for FN1, for which HIF-independent regulatory mechanisms are also described, 46 and for LOXL2.…”
Section: Discussionmentioning
confidence: 96%
“…33 Predeveloped TaqMan reagents were used for human fibronectin 1 (FN1, NM_002026), human lysyl oxidase-like 2 (LOXL2, NM_002318.2), and the housekeeper genes 18S rRNA, GAPDH, and ␤-actin (Applied Biosystems, Foster City, CA). The following oligonucleotide primers (300 nmol/L) and probe (100 nmol/L) were used for human CXCR4 (NM_003467.2), sense primer 5Ј-GGCCGACCTC-CTCTTTGTC-3Ј, antisense primer 5Ј-CAAAGTACCAGTTT-GCCACGG-3Ј, and fluorescence labeled probe (FAM) 5Ј-ACGCTTCCCTTCTGGGCAGTTGATG-3Ј; and for CXCL12 (NM_199168), sense primer 5Ј-ACCGCGCTCTGCCTCA-3Ј, antisense primer 5Ј-CATGGCTTTCGAAGAATCGG-3Ј, and fluorescence labeled probe (FAM) 5Ј-TCAGCCT-GAGCTACAGATGCCCATGC-3Ј.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…Recent publications also suggest a decline of VEGF-A expression in progressive diabetic nephropathy. 37 In a more general context, these findings are of significant importance because the expression of VEGF-A in the tubulointersititium is most likely to play a major role in neo-angiogenesis of peritubular capillaries, with reduced VEGF-A levels being responsible for peritubular capillary rarefaction, tubular atrophy, loss of functional nephrons, and impaired recruitment of endothelial progenitor cells. 23 The significance of these hypotheses is further supported by our results in which attenuated expression of VEGF-A and increased expression of HIF-1a together predicted outcome of chronic renal disease to a higher extent than well-established parameters, such as proteinuria, eGFR, or the degree of TAIF at the time of biopsy.…”
Section: Systems Biology Of Human Tubule Cells M Rudnicki Et Almentioning
confidence: 99%
“…Major sources of renal VEGF are tubular epithelial cells and podocytes, whereas endothelial cells and podocytes (acting in both autocrine and paracrine fashions) are major targets. Recent studies showed that renal levels of VEGF are altered in pathologic situations, such as chronic and acute renal ischemia, 12,13 diabetic-induced renal injury, 14,15 atherosclerosis, 16 or metabolic syndrome, 17 suggesting a potential pathologic role of this cytokine to promote profound microvascular dysfunctional and morphologic changes. Elegant seminal studies by the laboratories of Johnson and colleagues 18 and Basile and colleagues 19 showed that VEGF therapy reduced renal damage and protected the microvasculature in rodent models of chronic renal disease.…”
mentioning
confidence: 99%